Sustainable Strategies for Risk Management Process of Coca-Cola Company with Regard to Promote Climate Resilience Efforts and Agricultural Sustainability. Chosen Contexts - MROZEK, Michał (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023, 2023)
The paper regards the sustainable strategies for risk management process of Coca-Cola Company with regard to promote climate resilience efforts and agricultural sustainability. The fundamental aim of the paper is the analysis of the Coca-Cola Company in terms of agricultural sustainability. The company’s beverage production and packaging processes rely heavily on agricultural components. Enterprise’s efforts to promote climate resilience, water security, human rights, sustainable packaging, and economic development rely heavily on the use of sustainably produced foods. Adaptation strategies throughout its supply chain and in the communities that produce the company’s agricultural components will be greatly aided by the adoption of more sustainable agriculture methods as climate change causes more severe weather and higher water stress. The PSA was first implemented in 2021 to enhance the company’s prior Sustainable Agriculture Guiding Principles (SAGP) and accelerate its movement toward the ethical and environmentally responsible procurement of agricultural components. The paper is using of statistical, comparative, dynamics, and documentation analysis. The time scope of the study is 2020-2021, but in some aspects, it was broadened.